Isolation and characterization of hypocholesterolemic bioactive agent extracted from Monascus purpureus FTC5391 - Ajdari, Zahra (2012)
One of the basic causes of mortality in developed countries is cardiovascular disease,especially coronary heart disease. Control of blood cholesterol level is important to avoid cardiovascular disease. In this study the bioactive compound(s) of Monascus purpureus FTC5391 with hypocholesterolemic potential was investigated. In order to purify and identify the hypocholesterolemic bioactive agent of M. purpureus FTC5391 fermented product, cultivated via submerged fermentation in modified medium was sub-fractionated by solid phase extraction (SPE). The hypocholesterolemic active fraction in rats was selected for further purification by recycling preparative HPLC (RP-HPLC). The effective fraction significantly (P-value < 0.05) regulated the serum lipid-profile of hypercholesterolemic rats as compared with no treated control groups. This fraction increased the serum HDL-C (100%) and decreased the TC (42.6%), LDL-C (46%), TG (54.4%) levels as well as TC/HDL-C ratio (71.9%). Whereas, Atrovastatin, as a positive control, could regulate the rat serum lipid profile by increasing the serum HDL-C (37.5%) and decreasing the serum TC, LDL-C, TG levels and TC/HDL-C ratio 45.15%, 42%, 54.3% and 61.4%, respectively. MS spectrum of the pure effective fraction and its comparison with spectra library suggested the cyclopropane-carboxylic acid 4-dodecanoeil ester as a novel hypocholesterolemic agent. The obvious superiority of this novel compound to gulate the lipid profile in comparison to the atrovastatin and its ability to decrease the liver damage indicator enzymes, revealed the golden perspective of this novel molecule as a potent future hypocholesterolemic drug.